Socioenvironmental Vulnerability to Climate Change: Conditions of Coastal Municipalities in Pará State - Marcos Ronielly da Silva Santos; Maria Isabel Vitorino; Luci Cajueiro Carneiro Pereira; Marcia Aparecida da Silva Pimentel; Ana Flávia Quintão (Ambiente & Sociedade, 2021)
Abstract The aim of the current study is to analyze the vulnerability of coastal municipalities in Pará State, based on the integration of socioeconomic, epidemiological and climatic indicators. Data were combined to climate scenarios such as Representative Concentration Pathway (RCP) 4.5 and 8.5, depending on the Municipal Vulnerability Index (MVI). Results have shown that the Sensitivity (SeI) and Sociodemographic (SdI) Indices had strong influence on the current vulnerability of the investigated municipalities. The association between current vulnerability index and future climate change projections has shown that municipalities located in Marajó Island region are the most vulnerable ones - to the West of the study site, where MVI ranged from 1 (in Afuá) to 0.55 (in Soure), for scenarios 4.5 and 8.5, respectively. The current results can contribute to the effective adoption of public policies focused on prioritizing the most vulnerable municipalities and on preparing them to deal with adverse aspects of climate change.